2022
DOI: 10.33386/593dp.2022.1-1.975
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias personalizadas para la enseñanza en educación básica: estudio de revisión.

Abstract: Las Estrategias Personalizadas (EP) en la educación básica, son herramientas indispensables para los docentes en la atención individual de sus estudiantes teniendo en cuenta sus inteligencias, ritmos y estilos de aprendizaje, así como también sus necesidades educativas especiales, convirtiéndose en su reto, conllevando a dejar atrás la deshumanización, para convertirla en humanizante del hombre como centro y actor de su proceso de aprendizaje y autorrealización. Esta investigación es un estudio de revisión sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting that the distinctiveness of educational practice presents an unavoidable and significant challenge in the contemporary landscape (Lerís & Sein, 2011;UNESCO, 2017). Therefore, the conducted study characterises and describes elements and processes specific to personalised education (Aliaga, 2022;Coll, 2018;Lerís & Sein, 2011;Liu et al, 2017), developed within a sample of prominent primary education centers associated with pedagogical renewal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the distinctiveness of educational practice presents an unavoidable and significant challenge in the contemporary landscape (Lerís & Sein, 2011;UNESCO, 2017). Therefore, the conducted study characterises and describes elements and processes specific to personalised education (Aliaga, 2022;Coll, 2018;Lerís & Sein, 2011;Liu et al, 2017), developed within a sample of prominent primary education centers associated with pedagogical renewal.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a critical review of academic literature has identified certain elements that promote personalised learning, enrich teacher-student interaction, and improve certain aspects of learning, providing specific orientations, actions, and didactic strategies. Taken together, the following stand out: first, considering the students' interests in the design and development of the didactic process; second, identifying significant learning experiences for the student; and finally, promoting the learner's reflection and responsibility for the teaching and learning process (Aliaga, 2022;Coll, 2016;Huang, Liang, Su & Chen, 2012;Hwang, Sung, Hung & Huang, 2013;Liu, McKelroy, Corliss & Carrigan, 2017;Paz, 2017;Song, Wong & Looi, 2012;Wongwatkit, Srisawasdi, Hwang & Panjaburee, 2017;Xie, Chu, Hwang & Wang, 2019). With regards to this, the words of Engel and Coll (2022) are particularly interesting when they state that "the potential of a given learning personalisation strategy is conditioned by its confluence with others" (Engel & Coll, 2022: page 229).…”
Section: The Uniqueness In Educational Practice: Personalised Educationmentioning
confidence: 99%
“…In this sense, in recent decades, there has been a resurgence of pedagogical renewal centres in Spain, which aim to adapt the educational system to the needs of students by integrating methodologies and approaches focused on their personal, competential development and progress within the educational system (Beneyto, Carrete, Arregui & Domingo, 2023). These centres can be considered as catalysts of change that have significantly improved students' socio-emotional skills and academic performance through the implementation of innovative practices and resources adapted to the characteristics of the students (Aliaga, 2022).…”
mentioning
confidence: 99%